Multiple Sclerosis and the Risk of Cardiovascular Diseases: A Mendelian Randomization Study - Yang, Fangkun; Hu, Teng; He, Kewan; Ying, Jiajun; Cui, Hanbin (Frontiers in Immunology, 2022)
Background: Previous observational studies have implicated that multiple sclerosis (MS) is associated with cardiovascular diseases (CVDs). However, the causal relationship has not been fully elucidated. Objective: In the current study, we aim to estimate the effects of genetically determined MS on risk of CVDs. Methods: A two-sample Mendelian randomization (MR) study was performed to explore the causality. Genetic instruments were identified for MS from a genome-wide association study (GWAS) involving 115,803 individuals. Summary statistics data for CVDs were extracted from different GWAS meta-analysis study. MR analysis was conducted using inverse-variance weighted (IVW) method. Several sensitivity analyses were further performed to ensure the robustness of our results. Results: This MR study found suggestive evidence that genetic liability to MS was associated with a higher risk of coronary artery disease (CAD) [odds ratio (OR),1.02; 95% confidence interval (CI), 1.01-1.03; p = 0.03], myocardial infarction (MI) (OR, 1.03; 95% CI, 1.02-1.04; p = 0.01), heart failure (HF) (OR, 1.02; 95% CI, 1.01-1.03; p = 0.02), all-cause stroke (AS) (OR, 1.02; 95% CI, 1.01-1.03; p = 0.02) and any ischemic stroke (AIS) (OR, 1.02; 95% CI, 1.01-1.03; p = 0.04). A null-association was observed between MS and the other CVDs. Sensitivity analysis yielded little evidence of pleiotropy. Conclusions: This MR study provided suggestive evidence for the causal association of MS with increased risk of CAD, MI, HF, AS and AIS. However, no causal association was observed between MS and other subtypes of CVDs.